An economic evaluation of the monetary and psychosocial costs and benefits of emigration to the United States of America and its effects on households in the city of Matagalpa, Nicaragua (Revista Científica Tecnológica - ISSN: 2708-7093, 2023)
This research was developed with the objective of evaluating the social and economic impact of emigration to the United States of America on the well-being of Nicaraguan families in the first half of 2023 (both of the members who emigrated and those who stayed). Based on the bibliographic review and research objectives, it was decided in the theoretical and methodological framework that it was necessary to investigate the influence of push and pull factors on the decision to emigrate. The economic and psycho-social effect on the family and emigrants before, during, and after the emigration process was also investigated. Finally, the net benefit (benefits versus costs) of emigration was evaluated in a total way (the monetary jointly with the psycho-social aspect). To carry out the study, surveys were applied to a random sample of 30 family units in the city of Matagalpa whose members have emigrated in the last four years and five (5) emigrants residing in the United States. The results indicate that a large part of the family units surveyed, and the emigrants interviewed consider that costs are, in general, equal to or greater than the benefits. This happens because although emigration has had a monetary benefit, this benefit does not necessarily offset the costs associated with the psycho-social problems that it generates in the family unit. From this perspective, it can be concluded that emigration is not a desired good, but rather a necessary evil for families whose members are forced to emigrate.
Keywords: emigration; push and pull factors; economic effect; psycho-social effect; costs and benefits